Respuesta plástica a la luz y al agua en cuatro especies del género Quercus (IV Congreso Forestal Español, 2005)
El objetivo de este estudio es conocer el nivel de plasticidad fenotípica de plántulas de varias especies de Quercus a dos de los principales factores que regulan el crecimiento y la supervivencia de las plantas leñosas mediterráneas: la luz y el agua, así como determinar qué variables son más plásticas a uno u otro factor. Se cultivaron en condiciones controladas individuos de Quercus ilex subsp. ballota, Q. suber, Q. pyrenaica y Q. canariensis en tres tratamientos de luz (100, 25 y 3% de luz incidente) y con agua abundante. A partir de mediados de primavera, a una parte de los individuos se le suprimió el agua, de forma que se tuvieron dos tratamientos de agua (riego vs. no riego) dentro de cada tratamiento de luz. Se estudiaron distintas variables fisiológicas, como la tasa de fotosíntesis y respiración, el punto de compensación y de saturación a la luz, la conductancia estomática, la eficiencia instantánea en el uso del agua, la eficiencia fotosintética a la luz y la eficiencia en el uso del nitrógeno. También se estudiaron distintas variables morfológicas o estructurales, como el área foliar, el área específica foliar, las concentraciones de N y C y un índice de clorofila. La plasticidad de las variables estructurales al factor agua fue muy baja, mientras que el índice de plasticidad de las fisiológicas fue mayor. Con la luz, no se detectaron diferencias en los índices de plasticidad de las variables estructurales o fisiológicas. Estas diferencias se pueden explicar, por un lado porque la luz es un factor que ha condicionado el crecimiento y expansión de las hojas, afectando tanto a las variables estructurales como fisiológicas. Por el contrario, la falta de agua se puso de manifiesto cuando la planta había finalizado su crecimiento; así no respondieron a este factor modificando características estructurales, de gran componente ontogenético. Sin embargo, estas especies adaptadas a la sequía estival, sí tienen buen potencial de aclimatación a la falta de agua modificando características fisiológicas que le permiten optimizar la relación fotosíntesis/transpiración.

Relación entre composición y densidad de la cubierta vegetal leñosa y las características superficiales del suelo en Bosques Mixtos de Quercus del Sur de la Península Ibérica (Tendencias Actuales de la Ciencia del Suelo, 2004)
We studied the relationships between different estimates of the woody canopy density; different estimates of litter release and accumulation, and different soil properties (mainly soil reaction and macronutrient level) which have been recognised as potentially relevant for plant establishment and development in mixed Quercus forest from Natural Park “do Sudoeste Alentejano e Costa Vicentina”, Portugal (with Q. suber, Q. faginea as dominant tree species) and Natural Park “Los Alcornocales”, Spain (with Q. suber and Q. canariensis). We have found 1) A highly significant, quantitative, relationship between litter accumulation and overall canopy density. These relationships can be established either by using objective (but time-consuming) measures (by sampling or using ad hoc measuring devices) or by calibrated by-eye estimates of three simultaneous observers; 2) A significant relationship between some soil properties (N, P, ammonium) and both canopy density and litter accumulation. We conclude that these relationships are interesting in two ways: 1) They may allow to establish ‘ecotransfer functions’ for these forests (i.e. estimates o predictions about surface litter accumulation or surface values for soil properties, as organic carbon, N or P contents, by using quick field estimates of canopy density or even remote sensing estimates of canopy density), after suitable calibrations. 2) Since some soil chemical properties with known ecological relevance (e.g. C, N, P contents, soil reaction) in forest regeneration may change in a close relationship with other more studied, better known, ecological factors (light, moisture, temperature), attention should be paid to separate direct (e.g. light limitation) versus indirect (soil or litter mediated) effects of woody canopy when evaluating ecological responses at the understorey, while studying forest regeneration processes.

Diversidad biológica y sostenibilidad ecológica y económica de los sistemas adehesados (Ecosistemas, 2003)
Los bosques mediterráneos son sistemas naturales con una elevada diversidad biológica, que tiende a aumentar cuando son explotados para formar dehesas arboladas. Dentro de este sistema de explotación, la riqueza de especies varía en función de los efectos del manejo humano sobre la estructura de la vegetación, tanto subarbórea (presencia de cultivos de cereal o manchas de matorral) como arbórea (densidad de árboles). Estas tendencias se observan en varios grupos de organismos y para un amplio rango de escalas espaciales, y parecen deberse a la íntima coexistencia espacial en las dehesas de elementos faunísticos y florísticos forestales, asociados al arbolado y al matorral, y de elementos propios de zonas abiertas, asociados a los pastizales y cultivos sobre los que crecen los árboles. La coexistencia a escala de finca de distintos usos, así como la coexistencia de las dehesas y otros hábitats a escala regional, contribuyen al mantenimiento de especies adicionales. No obstante, se requieren perturbaciones como el fuego o el uso humano, que serían las causas últimas de esta diversidad. La diversidad biológica de las dehesas podría contribuir a su sostenibilidad económica si èsta es valorada adecuadamente por la sociedad. Además, se requerirían medidas adicionales que garantizasen situaciones temporales de menor diversidad pero indispensables para la regeneración del arbolado y la sostenibilidad ecológica de este peculiar sistema de explotación.

Regional differences in land use affect population performance of the threatened insectivorous plant Drosophyllum lusitanicum (Droseraceae) (Diversity and Distributions, 2003)
We analyse populations of the insectivorous plant Drosophyllum lusitanicum (L.) Link (Droseraceae) and their habitats throughout the species’ distribution range (Portugal, Spain and Morocco), and examine their relations. We have surveyed 32 populations and we analyse their demographic structures, accompanying plant communities (by TWINSPAN analyses), and relationships between population features and several edaphic and nonedaphic environmental variables (by multiple regression analyses). Plant communities, their ﬂoristic richness and degree of endemism change across the geographical range of Drosophyllum. Populations vary strongly in size, density and age structure. Their recruitment seems largely determined by competition with the surrounding vegetation, while only weak relationships were detected between population performance and other environmental factors. The demographic structure of populations exhibits a marked geographical differentiation, with populations becoming older and sparser towards the north-western part of the range. The largest and presumably most stable populations are mostly found in southern Spanish heathlands, which are nowadays scarcely affected by man. Moroccan populations suffer from browsing by cattle and experience an accelerated generation turnover, while most Portuguese populations occur in afforested areas and experience strongly reduced recruitment. The historical distribution range of Drosophyllum within its peculiar habitat has probably been relatively stable, but recent regional differences in human land use have resulted in present-day differences in population performance, as well as in types and degrees of threat across the three countries involved. Conservation strategies should take into account this range-wide variation and combine approaches on different spatial scales.

Soil seed bank and floristic diversity in a forest-grassland mosaic in southern Spain (Journal of Vegetation Science, 2003)
Soil seed bank and floristic diversity were studied in a forest of Quercus suber, a forest of Quercus canariensis and a grassland, forming a vegetation mosaic in Los Alcornocales Natural Park, southern Spain. The soil seed bank was estimated by the germination technique. In each community patch, diversity, woody species cover and herbaceous species frequency was measured. Three biodiversity components – species richness, endemism and taxonomic singularity – were considered in the vegetation and the seed bank. Forest patches had a soil seed bank of ca. 11 200-14 100 seed.m–2 and their composition had low resemblance to (epigeal) vegetation. The grassland patch had a more dense seed bank (ca. 31 800 seed.m–2 ) and a higher index of similarity with vegetation, compared with the forests nearby. The complete forest diversity was 71-78 species on 0.1 ha, including 12-15 species found only in the seed bank; the grassland species richness was higher (113 species on 0.1 ha). We discuss the role of soil seed banks in the vegetation dynamics and in the complete plant biodiversity of the mosaic landscape studied.

Biodiversity of woody species in oak woodlands of southern Spain and northern Morocco (Forest Ecology and Management, 1999)
Three biodiversity parameters ± species richness, endemic species richness and taxonomic singularity ± have been evaluated for the woody understorey of oak woodlands on sandstone-derived substrates, on both sides of the Strait of Gibraltar. There is a similarity in ¯oristic composition and ecological distribution of woody plant communities across the Strait. Nevertheless, we have detected signi®cant differences. These include a general reduction in species richness, number of endemic species and taxonomic singularity (at the community level), and a greater abundance of widespread, generalist species, on the southern side (Moroccan) communities, as compared to the north (Spanish ones). We interpret these differences as partly caused by the contrasting management of woodlands, with higher slashing and browsing pressure in Morocco.

Ecology and history of a wooded landscape in southern Spain (ECOLOGICAL HISTORY OF EUROPEAN FORESTS, 1998)
An extensive oak woodland, of about 1000 km(2), dominated by evergreen cork oak (Quercus suber) and semideciduous Q. canariensis, is found in southern Spain, near the Strait of Gibraltar, and contrasts with the paradigm of deforested Mediterranean mountains. Several factors, ecological, geographical and historical, have contributed to the origin and maintenance of this forested landscape. The rough relief and the acidic, nutrient-poor soils (derived from Oligo-Miocene sandstone) made this area unsuitable for cultivation. The oceanic influence favours the growth of oak trees. In particular, the cork oak is well suited to acidic soils and the humid Mediterranean climate. Three historical milestones seem relevant to the preservation of this woodland. Its location at a frontier during medieval times (thirteenth to fifteenth centuries) discouraged villages and reduced human pressure on the woodland resources. The rise of the value of cork helped to preserve the cork oak woodland during early nineteenth. century industrial times. contemporary consciousness about the conservation of woodland landscapes (somewhat unusual in the Mediterranean region) led to their designation as Los Alcornocales (meaning `The cork oak woodlands') Natural Park, devoted to the eco-development of the region.

Patterns of ecological, chorological and taxonomic diversity at both sides of the Strait of Gibraltar (JOURNAL OF VEGETATION SCIENCE, 1996)
Diversity relations in Mediterranean heathlands and the understorey of oak woodlands on sandstone-derived substrates were studied at both sides of the Strait of Gibraltar. Trends in species composition and cover were analysed by Detrended Correspondence Analysis; the first axis, assumed to reflect a main environmental gradient, was used to analyse the patterns of three aspects of community diversity. Species richness, i.e. number of species along a 100-m transect, shows a humpbacked trend along the gradient, with the highest values in the understorey of evergreen Quercus suber woodlands, associated with soils of intermediate fertility and moisture status. The number of endemic species is highest in open heathlands, associated with more extreme conditions of acid, infertile soils on exposed ridges. The taxonomic singularity, as measured by the inverse of the average number of species per genus at each site, is highest at the most fertile and moist sites occupied by semideciduous Q. canariensis woodlands. A comparison between northern (Spanish) and southern (Moroccan) sides of the Strait of Gibraltar shows a general concordance of the trends of woody plant communities along the main environmental gradient. However, significant differences of the southern samples are: (1) lack of some differential, habitat-specific species and greater abundance of wide spread generalists; and (2) a general reduction in species diversity, number of endemics and taxonomic singularity. We interpret these differences as affected partly by the smaller extent and fragmentation of sandstone areas in the south, and partly by the higher impact of slashing and grazing there.

Biodiversity components and conservation of mediterranean healthlands in Southern Spain (Biological Conservation, 1995)
Biodiversity is a complex issue which has frequently been extremely simplified both by equating it with species richness, and by addressing it at the level of regional floras or faunas. In this paper we carry out a detailed assessment of biodiversity for conservation of Mediterranean heathlands and related woodland understoreys on acidic ‘islands’ in the Gibraltar Strait region which are remarkable for their high species richness, high endemism and low ratio of species per genus. The relationship between the cover of woody plant species and environmental variables was studied by multivariate (DCCA) analysis of 30 samples. Species richness shows a unimodal relationship along the main environmental gradient primarily determined by physiological tolerance to low pH and ecological competition. Quercus suber woodland understoreys under intermediate environmental conditions are highest in species richness. Woody plant species are assigned to one of seven types of geographic ranges, and distributional spectra of community samples are represented. Open heathlands on nutrient-poor soils on mountain ridges are highest in endemism. Species distinctness was estimated as the inverse of the average number of species per genus (‘taxonomic singularity’) within the Mediterranean Basin, Ibero-North African and Southwestern Spain ranges. Quercus canariensis woodland understoreys on more fertile soils on valley bottoms present the highest taxonomic singularity. The analysis at the community level of the three proposed biodiversity components (species richness, endemism richness and taxonomic singularity) is interpreted with the aim of formulating sound conservation strategies of the communities examined. Although we use communities in the Gibraltar Strait area as a particular case study, we suggest that this methodology would help conservation efforts in other areas.

Estudio ecológico de los pastizales de dehesa en la provincia de Badajoz. Tipificación preliminar de la vegetación empleando el análisis de correspondencias (Pastos, 1977)
42 grasslands of Badajoz and Huelva provinces (Western Spain) were studied recording plant species frequencies with 10 quadrats (20 X 20 cm.) randomly distributed over 2 X 2 m. plots taken under the crown of Quercus rotundifolia trees. Soil samples collected on every plot were analysed for pH, orgainic matter, P, Ca, K and Na. Frequency matrix (80 plant species X 42 plots) was analysed by the method know as "Analyse des Correspondences" (BENZECRI, 1973). The two main components (accounting for about 20 % of the overall variation) sepárate plots into six recognizable groups (grassland types). A preliminary attempc to interpret those groups is made in terms of biotope (soil and substrate) differencies. The two main directions of variation found correspond to an eutrophization gradient (poor acidic versus rich basic soils) and to an erosión gradient (soil erosión versus pedogenesis). Secondary causes of variation are interpreted as due to lithology, climate and management. Further analysis of present data is currently under way.